2015
DOI: 10.1039/c5ce00776c
|View full text |Cite
|
Sign up to set email alerts
|

Progress in the synthetic and functional aspects of chiral metal–organic frameworks

Abstract: In this highlight, two aspects of chiral metal-organic frameworks, in particular synthetic approaches to achieve chiral MOFs and their applications, have been discussed. There has been considerable research advancement towards the synthesis of chiral MOFs by direct or indirect methods. More recently, homochiral MOFs have been exploited for valued applications such as asymmetric catalysis, enantioselective separation and recognition processes. Each part is subdivided with regard to the issues focused on and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(31 citation statements)
references
References 127 publications
(224 reference statements)
0
31
0
Order By: Relevance
“…Popplemeier and coworkers showed that even racemic mixtures can give chiral structures 19 and Morris showed that bulk homochirality could be induced in metal organic frameworks (MOFs) in the right solvent systems 20 . The number of MOFs 21,22 and zeolites 23,24 with chiral crystallographic structures is increasing, the possibility to extend and combine chirality at different hierarchies remains unclear. To date, there have been just a few examples of MOFs with chiral surfaces 25,26 or 3D twisted shapes 27 , where in the latter cases the chirality is induced by a template and is manifest at a morphological level.…”
mentioning
confidence: 99%
“…Popplemeier and coworkers showed that even racemic mixtures can give chiral structures 19 and Morris showed that bulk homochirality could be induced in metal organic frameworks (MOFs) in the right solvent systems 20 . The number of MOFs 21,22 and zeolites 23,24 with chiral crystallographic structures is increasing, the possibility to extend and combine chirality at different hierarchies remains unclear. To date, there have been just a few examples of MOFs with chiral surfaces 25,26 or 3D twisted shapes 27 , where in the latter cases the chirality is induced by a template and is manifest at a morphological level.…”
mentioning
confidence: 99%
“…Due to their large surface areas, diverse structures, and varied functions, MOFs have diverse potential applications in areas such as gas sorption, [80] chemical sensing, [81] photocatalysis, [82] separation, [83] and electrocatalysis. [84] Chiral MOFs not only possess the intrinsic features of MOFs, but also offer a chiral environment that is very important for applications in asymmetric catalysis, [85] chiral recognition, [86] and enantioselective adsorption and separation. [87] The methods for preparing chiral MOFs can be classified into three major groups.…”
Section: Chiral-mof-based Probesmentioning
confidence: 99%
“…Chiral MOFs can be built by using numerous distinct strategies, each of which has its individual advantages and disadvantages [42,43]. In this review, we have classified the synthesis of chiral MOFs broadly into two different classes, namely the straightforward method and the indirect method, which are based on the component used for creating chirality within MOFs.…”
Section: Synthetic Strategies Of Chiral Mofsmentioning
confidence: 99%